Reactive Oxygen Species Scavenging Sutures for Enhanced Wound Sealing and Repair. Issue 7 (5th May 2021) - Zhu, Jiafei; Jin, Qiutong; Zhao, He; Zhu, Wenjun; Liu, Zhuang; Chen, Qian
Abstract : Wound healing is a complex biological process including hemostasis, cell proliferation, and tissue remodeling, which is closely associated with the level of oxidative stress within the impaired skin. The excessive reactive oxygen species (ROS) generated in the injured site is detrimental to the wound‐healing process via a series of elicited effects such as cellular senescence, fibrotic scarring, and inflammation. Herein, a novel ROS‐scavenging suture is developed by coating the surgical sutures with gallic acid (GA)‐based nanoparticles (GANPs) for wound treatment. The obtained sutures coated with GANPs can effectively promote wound closure by maintaining the tension and decreasing the ROS level around the wound. Specifically, GANPs coating on the suture can effectively scavenge ROS, upregulate anti‐inflammatory molecules, and polarize macrophages to M2 phenotype around the wound area, due to the efficient antioxidant activities of GA, a type of low‐molecular‐weight tea polyphenol. Thus, the ROS scavenging sutures developed in this work significantly improve wound healing with enhanced wound closure, less inflammation reaction, and reduced formation of scars, which may serve as the promising suture for wound healing in various conditions. Abstract : A novel reactive oxygen species (ROS)‐scavenging suture is developed by coating the surgical sutures with gallic acid‐based nanoparticles (GANPs) for enhanced wound repair in both normal and diabetic wound. The obtained GANPs‐coating sutures can effectively promote wound closure by maintaining the tension, decreasing the ROS level, upregulating anti‐inflammatory molecules, and polarizing macrophages to M2 phenotype around the wound area.